PENINGKATAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE CO-OP CO-OP DALAM PEMBELAJARAN PKn KELAS V DI SDN 11 KOTO MARAPAK KECAMATAN PARIAMAN TIMUR KOTA PARIAMAN - Ramadani, Rika; Reinita, Reinita; Abidin, Zainal (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The research aims to improve the learning outcomes of Civics by using cooperative learning model co-op co-op type in class V SDN 11 Koto Marapak Kec.Pariaman Timur. The type of research is PTK, using a quantitative and qualitative approach. The result of research of RPP of cycle I average 72% increase in cycle II to 84%. In the teacher cycle aspect I average 72% increase in cycle II to 90%. In the student aspect, the first cycle I is 71% increase in cycle II to 82%. Student learning outcomes cycle I average 74, and on the second cycle increased to 85. KeyWords : results of study;Civics; cooperative learning model co-op co-op type